EVALUATION OF IT GOVERNANCE USING COBIT 2019 ON REGIONAL ASSET MANAGEMENT AGENCY OF DKI JAKARTA - Herliani, Meidina; Wella, Wella (LPPM Universitas Nusa Mandiri, 2024)
An adequate level of IT availability can obtained by implementing IT Governance, which pay attention to all related issues service readiness, including services and resources. This research aimed to assess the IT Governance capability at the Regional Asset Management Agency (BPAD), a government institution responsible for asset management. The study specifically focused on issues related to data and information management, including leadership and risk management challenges. Using the COBIT 2019 Framework, data were collected through interviews and observations. The respondent of this research are 4 who work in the Data and Information Sub-Sector and one Head of Asset Administration. The findings revealed that the EDM 05 process achieved a capability level of 4, surpassing the organization's target. However, the APO 08 and APO 12 processes were rated at level 2, highlighting areas in need of improvement. The study provides recommendations to enhance BPAD's performance and optimize its business activities.